VD_FINDINFO Jug / 2025 / 142 vom 18. Oktober 2024 - VD Tribunal cantonal (2024)
DÉCISION D'IRRECEVABILITÉ, DÉLAI, APPELCPP, EMPÊCHEMENT NON FAUTIF, RESTITUTION DU DÉLAI | 399 al. 3 CPP (CH), 403 al. 1 let. a CPP (CH), 94 CPP (CH)